A STUDY OF THE FUNCTION OF CODE MIXING IN THE BOLLYWOOD SONGS - Rizwan Freed, Ahmed; Khan, Tenzila; Younas Shahzad, Muhammad; Ullah, Hafeez (International Journal of Psychosocial Rehabilitation, 2020)
Code mixing and code switching is a common feature of the conversation in the multilingual society like the Indian Subcontinent. Even the songs in which language has been chosen carefully to have no exception. In the present study, the phenomenon of code mixing and code switching in the Bollywood music has been investigated qualitatively. Twenty-nine songs from the five Film Fare award winner movies of the Bollywood from 2105 to 2019 in the category of the music have been selected and the function of the code mixing and code switching in those songs has been investigated. First of all, the qualitative data was` quantified. In 58.62% songs English, Punjabi or some other language has been mixed with the Hindi/Urdu language. English has been mixed in party songs or in the songs of union of the hero and heroine or in fast songs. In sad and serious songs or the songs of separation, English has not been mixed while Punjabi has been used sometimes in such songs. Out of twenty-nine songs, there are only eight songs in which Hindi/Urdu language has been used without mixing of any other language. All these songs except one song, are sad and serious songs. In this data, four songs have been sung in other languages other than Hindi/Urdu. Amon these four songs, two songs have been sung in Punjabi along with a lot of mixing of English. Both songs are very fast and have been sung in very happy mood. So, the mixing of English in sad and serious songs has very minimum scope in the Bollywood music while in fast party songs or the songs of the union, the mixing of the English language is a quite regular phenomenon in the Bollywood music.